Women in the world's legal professions - Schultz, Ulrike; Shaw, Gisela (Oñati international series in law and society., 2003)
Women lawyers, less than a century ago still almost a contradiction in terms, have come to stay. Who are they? Where are they? What impact have they had on the profession that had for so long been a bastion of male domination? These are key questions asked in this first comprehensive study of women in the world''s legal professions. Answers are based on both quantitative and qualitative analyses, using a variety of conceptual frameworks. 26 contributions by 25 authors present and evaluate the situation of women in the legal profession in both common and civil law countries in the developed wor.